2009
DOI: 10.12702/1984-7033.v09n04a12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability for mineral concentration of Eruca sativa L. and Diplotaxis tenuifolia L. accessions

Abstract: -Eruca sativa L. (rocket or arugula) and Diplotaxis tenuifolia L. (perennial wall-rocket)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
9
0
4
Order By: Relevance
“…As in this study, Bozokalfa et al (2009) reported that N had a positive correlation with P and Cu, and also found that N had a positive relationship with K, Ca, Fe, Zn and Mn. Many of the other correlations found by Bozokalfa et al (2009) also showed similarity with the findings of this study.…”
Section: Resultssupporting
confidence: 76%
“…As in this study, Bozokalfa et al (2009) reported that N had a positive correlation with P and Cu, and also found that N had a positive relationship with K, Ca, Fe, Zn and Mn. Many of the other correlations found by Bozokalfa et al (2009) also showed similarity with the findings of this study.…”
Section: Resultssupporting
confidence: 76%
“…The "ionome", or nutrient signature, is the elemental composition of an organism [1], which may vary with genotypic traits and phenotypic plasticity [2,3]. Low phenotypic plasticity of a species may restrain its abundance and productivity to specific ecological niches.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that amounts of K, Mn, and Zn might be increased by selecting convenient genotypes of the Eruca sativa L. and Diplotaxis tenuifolia L. plants (Bozokalfa et al, 2009). Brown et al (2012) investigated genetic variation among advanced potato breeding clones for tuber Ca and Mg amounts and the extent of genotype × environment interactions on these characteristics.…”
mentioning
confidence: 99%